Metabolomic profiles of the liquid state fermentation in co-culture of Eurotium amstelodami and Bacillus licheniformis - Wang, Yunsheng; Chen, Yincui; Xin, Jiankang; Chen, Xianjing; Xu, Tingyan; He, Jiefang; Pan, Zhangxu; Zhang, Chuanbo (Frontiers in Microbiology, 2023)
As an important source of new drug molecules, secondary metabolites (SMs) produced by microorganisms possess important biological activities, such as antibacterial, anti-inflammatory, and hypoglycemic effects. However, the true potential of microbial synthesis of SMs has not been fully elucidated as the SM gene clusters remain silent under laboratory culture conditions. Herein, we evaluated the inhibitory effect of Staphylococcus aureus by co-culture of Eurotium amstelodami and three Bacillus species, including Bacillus licheniformis, Bacillus subtilis, and Bacillus amyloliquefaciens. In addition, a non-target approach based on ultra-performance liquid chromatography time-of-flight mass spectrometry (UPLC-TOF-MS) was used to detect differences in extracellular and intracellular metabolites. Notably, the co-culture of E. amstelodami and Bacillus spices significantly improved the inhibitory effect against S. aureus, with the combination of E. amstelodami and B. licheniformis showing best performance. Metabolomics data further revealed that the abundant SMs, such as Nummularine B, Lucidenic acid E2, Elatoside G, Aspergillic acid, 4-Hydroxycyclohexylcarboxylic acid, Copaene, and Pipecolic acid were significantly enhanced in co-culture. Intracellularly, the differential metabolites were involved in the metabolism of amino acids, nucleic acids, and glycerophospholipid. Overall, this work demonstrates that the co-culture strategy is beneficial for inducing biosynthesis of active metabolites in E. amstelodami and B. licheniformis.